2003
DOI: 10.1007/s10067-003-0792-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hand osteoarthritis on grip and pinch strength and hand function in postmenopausal women

Abstract: The aim of the study was to investigate the effect of osteoarthritis on hand function in postmenopausal women. One hundred patients with hand OA and 70 healthy volunteers as controls were evaluated. Grip and pinch strength measurements and Dreiser's functional index were used for hand function. Pain was assessed by a visual analog scale, and tenderness was assessed by palpation and scored, depending on the severity of tenderness, as 0, 1 or 2. Heberden's and Bouchard's nodules and joint involvement were also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 15 publications
4
97
0
6
Order By: Relevance
“…Studies support an association of advanced age, female sex, family history, and increased BMI with CMC OA [2,6,16,30]. Pinching tasks are especially uncomfortable for patients with early OA, and patients with CMC and distal interphalangeal arthritis have been shown to have lower pinch and grip strength [1,5,8,17,24]. The extent to which this weakness during functional tasks informs the diagnosis of early CMC OA has been preliminary but not rigorously quantified in the literature [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies support an association of advanced age, female sex, family history, and increased BMI with CMC OA [2,6,16,30]. Pinching tasks are especially uncomfortable for patients with early OA, and patients with CMC and distal interphalangeal arthritis have been shown to have lower pinch and grip strength [1,5,8,17,24]. The extent to which this weakness during functional tasks informs the diagnosis of early CMC OA has been preliminary but not rigorously quantified in the literature [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…The first CMC joint is frequently affected by osteoarthritis (OA), a degenerative condition resulting in deterioration of the joint surfaces and eventual bone remodeling. 2 The consequence of CMC joint OA is severe pain, leading to considerable limitations in function and disability, and a substantial societal burden. 2,15,42,44 Patients with CMC joint OA represent the cohort of individuals with upper extremity arthritis most likely to undergo surgical intervention.…”
mentioning
confidence: 99%
“…2 The consequence of CMC joint OA is severe pain, leading to considerable limitations in function and disability, and a substantial societal burden. 2,15,42,44 Patients with CMC joint OA represent the cohort of individuals with upper extremity arthritis most likely to undergo surgical intervention. 3 However, previous studies examining the effectiveness of surgical intervention have reported varied levels of benefits in terms of pain reduction and improved function, and have demonstrated an adverse event rate of between 10% and 22%, depend-T T STUDY DESIGN: Double-blind, randomized controlled trial.…”
mentioning
confidence: 99%
“…Many studies have reported that grip strength is negatively affected by various forms of arthritis [28][29][30][31][32]. A study by Bagis et al (2003) scores of those with osteoarthritis on both hands were significantly lower than those without osteoarthritis and would meet the sarcopenia criteria used by the EWGSOP for muscular strength (grip strength <20kg) [6]. Therefore, since a cut-point of <20kg…”
Section: Discussionmentioning
confidence: 99%